The Influence of Religiosity on Accounting Student Academic Cheating - Wardani, Dewi Kusuma; Puspitasari, Dita (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to examine the effect of religiosity on academic fraud among accounting students. The sample used in this study were students of accounting at the Faculty of Economics at Tamansiswa University, Yogyakarta. The sampling method used is convenience sampling. The samples obtained had 101 respondents. The results showed that religiosity has a negative effect on accounting students' academic fraud.